Safety of performing CT angiography in stroke patients treated with intravenous thrombolysis. Issue 7 (3rd December 2009) - Aulický, P; Mikulík, R; Goldemund, D; Reif, M; Dufek, M; Kubelka, T
Abstract : Objective: Exposure to contrast agents may cause nephrotoxicity. The safety of performing CT angiography without having knowledge of the baseline creatinine level in stroke patients treated with tissue plasminogen activator (tPA) has not been established. Methods: This is an observational cohort study, with a historical control group to evaluate the safety of CT angiography performed before tPA treatment given within 3 h of symptom onset. The CT angiography group represents all patients treated with tPA between September/2003 and November/2007 who had CT angiography. The control group consists of all patients treated with tPA between January 1999 and August 2003 when CT angiography was not performed. The primary outcome was a creatinine increase in 24–72 h compared with baseline; the secondary outcome was a creatinine increase by ≥44 μmol/l in 24–72 h and the incidence of symptomatic intracerebral haemorrhage (sICH). Results: Baseline parameters between the CT angiography group (164 patients, age 70±11; 91 male) and the control group (77 patients, age 67±11; 45 male) were similar. In the CT angiography group, the mean creatinine increase was −0.89 mmol/l and in the control group 2.2 mmol/l (p=0.42). A creatinine increase of ≥44 μmol/l occurred in five patients (3%) in the CT angiography group and in three patients (4%) in the control group (p=0.50). Also, in the CT angiography group, eight patients (5%) had sICH as compared with three patients (4%) in the control group (p=0.73). Conclusion: Contrast agents given for CT angiography, performed in patients with normal and abnormal creatinine level, neither caused renal injury nor interfered with the safety of tPA treatment.